Learner anxiety and EFL learning: A study of tertiary students' and teachers' perceptions in Taiwan - Chuang, Chieh-Hsiang (2015)
This study investigated Taiwanese university students’ and teachers’ perceptions of foreign language anxiety in the English as a foreign language (EFL) classroom. The main aims were: (a) to identify the situations, sources, effects of, and coping tactics for the anxiety of Taiwanese tertiary students and (b) to examine tertiary English teachers’ perceptions of their students’ anxiety and how they deal with it. An anxiety scale, the ELCAS, was first administered to English major and non-English major students to identify the ten most anxious students in each group for individual semi-structured interviews. English majors’ teachers and those of non-English majors also had semi-structured interviews. The students’ degree of anxiety was statistically analyzed and revealed by IBM SPSS 20. The interview data from students and teachers were transcribed verbatim, coded, categorized, and then thematized in order to obtain the patterns of their perceptions on the issues. The summarized findings are:  The English major and non-major students were similar to each other in the situations, effects of, and coping strategies for anxiety, except for the sources of their anxiety.  The students reported a number of strategies, but most of these only helped them cope with individual anxious situations, not the root causes of their anxiety.  The English majors and their teachers had similar perceptions of anxiety in class although the latter revealed less specific situations than the former.  The similarity was also quite high between the non-majors’ and their teachers’ perceptions of their anxiety. These teachers also reported relatively broader contexts than their students.  Both groups of teachers employed quite diverse strategies for reducing students’ anxiety. Their tactics demonstrated their attempts to address problems at their sources.